Towards a viable financial service sector : the role of risk assesment - Douglas, Seymour ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Addresses the question of the risk associated with traded assets by examining the likelihood of debt repayment difficulties. Discusses the role of adequate and effective risk assessment in developing viable capital markets.